Pharmaceutical Care in Goiânia: inclusion of the pharmacist in the Family Health Strategy - Provin, Mércia Pandolfo; Campos, Andréa de Paula; Nielson, Sylvia Escher de Oliveira; Amaral, Rita Goreti (Saúde e Sociedade, 2010)
In agreement with the Brazilian National Drug Policy, the School of Pharmacy of Universidade Federal de Goiás, in partnership with the Municipal Health Department of Goiânia, state of Goiás, created and implemented a university development project suggesting the inclusion of the pharmacist in the Family Health Strategy. Meetings were held in order to introduce the project to the respective primary care units and to train the teams of pharmacists in the exercise of pharmaceutical assistance. In the 12 months of the project, 50 patients with hypertension (70% female), with average age of 50, were assisted. Among those, 40 (80%) presented more than one associated illness and 46 (92%) used 2 or more drugs, simultaneously prescribed. In the study, 154 Medication-Related Problems (MRP) were detected, with an incidence of 3.1 MRP per patient. The most frequent MRP was lack of therapeutic efficacy (49%), and 26.3% of these were caused by lack of treatment adherence. It can be concluded that the health care problems caused by lack of pharmacotherapy efficiency assume important proportions. Pharmaceutical Care as a strategy of Pharmaceutical Assistance in Family Health can be an efficient alternative to obtain better clinical and economic results, and to improve the healthcare provided for users of Brazil's National Health System.